Range contraction and increasing isolation of a polar bear subpopulation in an era of sea‐ice loss. Issue 4 (18th January 2018) - Laidre, Kristin L.; Born, Erik W.; Atkinson, Stephen N.; Wiig, Øystein; Andersen, Liselotte W.; Lunn, Nicholas J.; Dyck, Markus; Regehr, Eric V.; McGovern, Richard; Heagerty, Patrick
Abstract: Climate change is expected to result in range shifts and habitat fragmentation for many species. In the Arctic, loss of sea ice will reduce barriers to dispersal or eliminate movement corridors, resulting in increased connectivity or geographic isolation with sweeping implications for conservation. We used satellite telemetry, data from individually marked animals (research and harvest), and microsatellite genetic data to examine changes in geographic range, emigration, and interpopulation connectivity of the Baffin Bay (BB) polar bear ( Ursus maritimus ) subpopulation over a 25‐year period of sea‐ice loss. Satellite telemetry collected from n = 43 (1991–1995) and 38 (2009–2015) adult females revealed a significant contraction in subpopulation range size (95% bivariate normal kernel range) in most months and seasons, with the most marked reduction being a 70% decline in summer from 716, 000 km 2 (SE 58, 000) to 211, 000 km 2 (SE 23, 000) ( p < .001). Between the 1990s and 2000s, there was a significant shift northward during the on‐ice seasons (2.6 ° shift in winter median latitude, 1.1 ° shift in spring median latitude) and a significant range contraction in the ice‐free summers. Bears in the 2000s were less likely to leave BB, with significant reductions in the numbers of bears moving into Davis Strait (DS) in winter and Lancaster Sound (LS) in summer. Harvest recoveries suggested both short and long‐term fidelity to BB remained high over both periods (83–99% of marked bears remained in BB). Genetic analyses using eight polymorphic microsatellites confirmed a previously documented differentiation between BB, DS, and LS; yet weakly differentiated BB from Kane Basin (KB) for the first time. Our results provide the first multiple lines of evidence for an increasingly geographically and functionally isolated subpopulation of polar bears in the context of long‐term sea‐ice loss. This may be indicative of future patterns for other polar bear subpopulations under climate change. Abstract : Our results provide the first multiple lines of evidence for an increasingly geographically and functionally isolated subpopulation of polar bears in the context of long‐term sea‐ice loss. This work is important and timely because large‐scale sea‐ice loss across the Arctic is predicted to continue and this is expected to have multiple impacts on polar bears.